Geoelectric resistivity sounding for deciphering hydrogeology and locating deep tubewell installation sites in Puroshava area of Bagerhat, Bangladesh - Woobaidullah, A. S.M.; Uddin, Mohammad Zohir (Journal of Nepal Geological Society, 2011)
The study area includes Bagerhat Pouroshava and its surroundings under Bagerhat Sadar Upazila covering an area of 7.53 sq. km with a population of about 50,000. Bagerhat is a coastal district and the subsurface geology is complicated. As in other areas of the coastal belt the quality of ground water in the area is also variable. For ground water development in the study area the shallow aquifer is not suitable as the water is mostly saline to brackish except some isolated fresh water pockets of limited yielding capacity. The deep aquifer is also not very homogeneous in water quality. In the northwestern part it bears fresh water but water quality deteriorates south-southeast with higher depth of occurrence. A comprehensive study is carried out to demarcate the aquifers and to judge the water quality to find the suitable location of the deep tube wells in Bagerhat Pouroshava area. Fifteen geoelectric soundings have been executed in the study area using Schlumberger configuration with maximum spreading of 1200 m. Based on the vertical electrical sounding interpretation results the subsurface sequence is divided into following geoelectric units: The top unit has resistivity less than 5.0 Ωm with a thickness of 1.5 to 20 m and represents the top clay silty/sandy clay layer. The second geoelectric unit represents a very fine to medium sand with thin clay lenses and resistivity varying from 5.0 Ωm to more than 100.0 Ωm with a thickness of 16 to 135 m. The resistivity of the following unit ranges from l.40 Ωm to 4.8 Ωm and thickness varies from 100 m to more than 300 m. The deepest geoelectric unit shows resistivity from 8.0 Ωm to 18.0 Ωm and represents the deep aquifer. The depth to the aquifer varies from 235 m to 355 m. The most suitable site for groundwater development from the deep aquifer is in the vicinity of East Saira of Shatgambuj union.